SPECIFICATIONS FOR THE MODEL 40 SNOWPLANE - Pierce, N. E. (1963)
Outline specifications for procurement of special equipment for compaction of snow in polar regions are being prepared by the Laboratory. This technical note contains the specifications for the Model 40 snowplane presented in the Naval Civil Engineering Laboratory Technical Report R-110 (AD-250 532) Snow Compaction Equipment Snowplanes. This unit which is a ski-mounted, towed- type piece of equipment, is used for leveling and grading natural and compacted- snow areas. Its 40 foot span makes it suitable for use on medium-wave sastrugi, or wind-driven snow, where the crest-to-crest distance is less than 40 feet.